Man's perception of paternity during the postpartum gestation period (Research, Society and Development, 2020)
Paternity implies transformations, the man, in this path of his life, has never lived directly with the practices of caring for a pregnant, postpartum woman and, consequently, a newborn, excluding themselves from such functions, leaving under the responsibilities of women, relatives and friends. Therefore, the present study aimed to analyze the perceptions of men about their attributions of father during the period from pregnancy to postpartum. This is an exploratory-descriptive field study with a qualitative approach, conducted with 11 parents in the Basic Health Units (BHU) of the city of São João do Sóter-MA. Data collection was performed through semi-structured interviews with closed and open questions. Data were analyzed according to the content analysis proposed by Bardin. As for the results, the news of fatherhood, for some men, turns out to be a difficult barrier to transpose, because for them the act of being a father is simply being the provider of financial resources in the family bond. Reality shows that most parents do not actively participate in pregnancy in the first days of their child's life; and seeking to understand the moment, the father isolates himself trying to answer his questions. The present study made it possible to highlight the real conception of the man / father regarding the pregnancy / puerperal process and suggests that the Primary Health Care nurses reflect on the findings of this research. Finally, other related works are necessary for a better understanding of the subject studied here.